2004
DOI: 10.1111/j.1601-0825.2004.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral findings in coeliac disease and Sjögren's syndrome

Abstract: The co-occurrence of CD and SS should be recognized because of its effects on dental and oral mucosal health. A lower salivary gland inflammatory focus score and higher salivary flow rate in CD + SS than in SS suggests that a gluten-free diet treatment may alleviate autoimmune inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 31 publications
5
34
2
5
Order By: Relevance
“…In relation to the salivary flow changes and their effects in the oral cavity of patients with CD, some authors reported that celiac patients have a higher predisposition to xerostomia [41]. However, some authors have reported that CD does not affect the salivary flow, but affects its composition, because the albumin values, IgA, IgM, amylase and myeloperoxidase were altered [42].…”
mentioning
confidence: 98%
“…In relation to the salivary flow changes and their effects in the oral cavity of patients with CD, some authors reported that celiac patients have a higher predisposition to xerostomia [41]. However, some authors have reported that CD does not affect the salivary flow, but affects its composition, because the albumin values, IgA, IgM, amylase and myeloperoxidase were altered [42].…”
mentioning
confidence: 98%
“…Xerostomic patients complain mostly about burning mouth, loss of taste, difficulty in swallowing, unpleasant taste and odor, oral dryness, increased thirst, chewing, speaking, gastroesophageal reflux, oral breathing, malfunction of removable prosthesis and sensitive teeth (49)(50)(51)(52)(53)(54) with the interaction of the glandular cell with its extracellular matrix sectional descriptive observational study that patients with SS have voice, speech and swallowing abnormalities, not only associated with to xerosis but perhaps also to neurological abnormalities, probably secondary to the syndrome (55). On the other hand, subjective xerostomia has been reported in higher percentages (75.18% to 91.84%) in patients with SS (56).…”
Section: Xerostomia and Treatmentmentioning
confidence: 99%
“…The salivary gland dysfunction seems to be caused by a progressive lymphocytic infiltration of the salivary glands, with subsequent inflammatory reaction that causes acinar atrophy and proliferation of connective tissue. The common symptoms are: dry mouth, sore mouth, increased thirst, loss of taste, difficulty in swallowing, chewing and talking, mouth breathing, bad taste and odor, increased sensitivity of teeth, gastroesophageal reflux and malfunctions of prosthesis (8,9). In addition, because of the immunological and microbiological changes in the oral cavity due to the lack of production of saliva, it is possible to observe an oral candidiasis (10).…”
mentioning
confidence: 99%